A MULTIDIMENSIONAL SUBDIFFUSION MODEL WITH CHEMOTAXIS - Bambang Hendriya Guswanto (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2019)
The mathematical model for subdiffusion process with chemotaxis proposed by Langlands and Henry [1] for the one-dimensional case is extended to the multi-dimensional case. The model is derived from random walks process using a probability measure on a n-multidimensional unit ball $S^{n-1}$.